Peculiarities of the Image of Correctional Agencies and Employees - Cimalanskaitė-Kazlauskienė, Violeta; Valickas, Gintautas (Teisė, 2020)
The article examines the character, similarities and differences of the image (or its separate aspects) of correctional agencies and employees perceived by the employees of correctional agencies (n = 342), convicts (n = 361) and the general public representing different age groups (n = 1023), as well as the relations among the image of correctional agencies and employees, experience accumulated by participants, and sociodemographic characteristics.
Keywords: correctional agencies; environmental, service, and social aspects of the image; similarities and differences of the perceived image; relations among the image and socio-demographic characteristics